HEATHCLIFF’S PERSONALITY DEVELOPMENT IN EMILY BRONTE’S WUTHERING HEIGHTS - Triastuti, Verawati (LANTERN (Journal on English Language, Culture and Literature), 2015)
This thesis will discuss about Heathcliff’s personality development in the novel Wuthering Heights by Emily Bronte. The purpose of this thesis is to analyze how and why the character’s personality develops. The writer uses characters, setting, and conflicts for intrinsic theory and Alfred Adler’s Individual Psychology for extrinsic theory. For the methodology, the writer uses library research methodology and psychological approach. The result shows that social interest, inferiority complex, goal orientation, and superiority complex give many infuences in developing Heathcliff’s personality so that he can take over Wuthering Heights and Thrushcross Grange. In the conclusion, Heathcliff comes as the most dominant and superior character by his personality development.